WORK SAFETY RISK MANAGEMENT TOWARDS ZERO ACCIDENT IN FASHARKAN SURABAYA - Susminarto Edy Herlambang; Wawan Kusdiana; Priiyadi Hartoko (Indonesian Naval Technology College STTAL, 2022)
Occupational health is an element of health related to the work environment and work, which can directly orindirectly affect work efficiency and productivity. Meanwhile, work safety is the main means to prevent workaccidents that can cause harm in the form of injury or injury, disability or death, property loss, damage toequipment or machinery and environmental damage widely. In essence, Occupational Safety and Health (K3) isan effort to create protection and security from various risks of accidents and hazards, both physical, mental andemotional to workers, companies, communities and the environment. In addition, occupational safety and healthis expected to create work comfort and high work safety as stated in PerKasal Number 26 of 2018 concerningOccupational Safety and Health in the Indonesian navy. This study aims to find out what types of accidents havea high risk in Fasharkan Surabaya, find out what impacts can be caused by high risk accidents and obtain stepsthat can be taken to reduce work accidents at Fasharkan Surabaya by using the Formal Safety Assessment (FSA)Method. There are four types of accidents that occur in Fasharkan Surabaya with the highest starting risk ranking,namely human accidents with work equipment, human accidents with property, human accidents with worksystems and human accidents with the environment. The impact of the four accidents caused substantial materiallosses. To reduce the risk of the three types of accidents, the lowest Implied Cost of Averting a Risk (ICAR)measurement is carried out for each risk reduction option. The risk mitigation carried out is providing training forGeneral K3 Experts, Electricity & Generators who have an ICAR of 92 million rupiahs, training of Fire K3 Officerswho have an ICAR of 15.75 million rupiahs, Implementation of Work SOPs and Tightening of Supervision whichhas an ICAR of 12.5 million rupiah, and Procurement of Work Safety Equipment in the work area of workshopsand ships as well as Personal Protective Equipment for each worker who has an ICAR of 53.5 million rupiah.Keywords: Formal Safety Assessment (FSA), Risk Assessment, Work Accident.